2020
DOI: 10.3390/met10101367
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Evaluation of the Influence of Different Material and Process Parameters on the Heat Transfer Coefficient in Gravity Die Casting

Abstract: Local heat transfer in gravity die casting is of great importance for precision in terms of distortion, mechanical properties, and the quality of the castings due to its effect on solidification. Depending on contact conditions such as liquid melt to solid mold, a gap between mold and component, or contact pressure between casting and mold as a result of shrinkage, there are very large differences in heat transfer. The influences of mold material, mold coating and its influence of aging, mold temperature contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The use of two oil temperature control units (type 1502/12 by Thermobiel Apparatebau GmbH, Gladbeck, Germany) with a total of four circuits, that can be set up independently from ambient up to 350 • C medium temperature and with a flow rate of 16 l/min each, enables full thermal control. The die coating was selected to be KS-81 (by Hüttenes-Albertus, Düsseldorf, Germany) from the previous works [1][2][3]. The measuring devices to measure the relative movement of the part and the contact pressure were also adopted from these previous test setups, with which the gap and contact pressure dependent heat transfer coefficients were determined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of two oil temperature control units (type 1502/12 by Thermobiel Apparatebau GmbH, Gladbeck, Germany) with a total of four circuits, that can be set up independently from ambient up to 350 • C medium temperature and with a flow rate of 16 l/min each, enables full thermal control. The die coating was selected to be KS-81 (by Hüttenes-Albertus, Düsseldorf, Germany) from the previous works [1][2][3]. The measuring devices to measure the relative movement of the part and the contact pressure were also adopted from these previous test setups, with which the gap and contact pressure dependent heat transfer coefficients were determined.…”
Section: Methodsmentioning
confidence: 99%
“…The long-term goal of this sub-project, on which the work presented here is based on, is to improve component precision in permanent mold casting by creating a knowledge base in the areas of distortion and hot cracking, and furthermore, the development of corresponding concepts for their prediction, influencing, and minimization. The heat transfer coefficient (HTC) between mold and component, which has already been considered as a possible major influencing factor, was analyzed in this project in several separate studies [1][2][3]. In addition to these primarily experimental studies, in closely related subprojects, the working group is developing numerical methods to advance the coupled thermomechanical simulation on both the macroscale and the microscale [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that the applied pressure will affect the interface heat transfer coefficient between the metal melt and the metal die [ 47 , 48 , 49 , 50 , 51 ]. It is generally believed that the liquid contacts the metal surface more closely after the melt is pressurized.…”
Section: Methodsmentioning
confidence: 99%
“…Here, the correct representation of heat transfer coefficients over time, including effects like the formation of gaps between the casting and the die, remains an area of research [281]. This is illustrated by the fact that two contributions to the present Special Issue are related to the topic [282,283].…”
Section: Smart Castingsmentioning
confidence: 97%
“…The studies by Wolff et al [283] and Kouki et al [282] are linked to virtual casting and simulation approaches, as they both consider the heat transfer coefficient (HTC), a crucial though difficult to determine parameter in casting. Kouki et al propose and evaluate a tool for measuring time-dependent HTCs in permanent mold casting.…”
Section: Contributions To the Special Issuementioning
confidence: 99%